Impact of Heat Treatment on Microstructure Evolution in Grey Cast Iron EN-GJL-300 - Peter Petruš; Igor Barényi; Jozef Majerík; Michal Krbata; Marcel Kohutiar; Ingrid Kovaříková; Martin Bilka (Metals)
This work investigated changes in the microstructure and local mechanical properties after the application of selected heat treatments to EN-GJL-300 grey cast iron. The main goal was to optimize heat treatment to achieve increased mechanical properties and subsequently wear resistance. The heat and heat–mechanical treatment were investigated by using a dilatometer as a physical simulator of treatment on real samples. Continuous cooling with three different rates and two other non-continuous treatments (austempering and ausforming) were used to treat the experimental samples. The research was focused on modification of the matrix microstructure, initially pearlitic. No change in the shape or morphology of the graphitic lamellae was required to preserve the damping properties. The results showed that, in terms of the specified conditions, heat treatment with continuous cooling at a rate of 10 °C s−1 appeared to be optimal. This variant showed the presence of bainite and martensite in the microstructure with high hardness measured by nanoindentation as well as the optimal value of general Brinell hardness.